The Comparison of Ayatollah Javadi Amoli, Ayatollah Mesbah Yazdi and Dr. Golshani's Religious Scienc - nazila akhlaghi; مهدی حسین زاده یزدی (حکمت اسرا, 2017)
The religious science is epistemic systems about the real world. The study of the philosophical foundations of science and the principles of theology is the first step towards the establishment of religious science. The emergence of the term religious science in the country's scientific community has become the center of some controversy, so that we encounter a number of contradictions among proponents and opponents. Given the extent of the controversy, the fact that the mere expression of the acceptance or non-acceptance of religious science by the thinkers, due to the various statements, does not clearly trace the theory of scholars. Frequent recurrences of views give rise to controversy and rigidity. Among those who believe in the possibility of religious knowledge, due to the importance of the theory of Ayatollah Javadi Amoli, Ayatollah Mesbah Yazdi and Dr. Golshani, we compared their theories of religious science and based on this, pointed out the position of reason and revelation in the views of each of these thinkers. This article seeks to make a step towards the clarity of religious science by comparing views.